2002
DOI: 10.1094/phyto.2002.92.8.816
|View full text |Cite
|
Sign up to set email alerts
|

Involvement ofBeet western yellows virus,Cauliflower mosaic virus, andTurnip mosaic virusin Internal Disorders of Stored White Cabbage

Abstract: Experiments over two growing seasons clearly showed that Turnip mosaic virus (TuMV) infection was associated with internal necrosis (sunken necrotic spots 5 to 10 mm in diameter) and Beet western yellows virus (BWYV) infection was associated with collapse of leaf tissue at the margins (tipburn) in heads of stored white cabbage (Brassica oleracea var. capitata). Virtually no tipburn was seen in cv. Polinius, whereas cv. Impala was affected severely. Internal necrotic spots were seen in both cultivars. BWYV appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 30 publications
0
17
0
5
Order By: Relevance
“…In an extensive survey conducted in many countries, TuMV was found to be the second most important virus after Cucumber mosaic virus (Tomlinson and Ward, 1987). Moreover, the incidence of TuMV may be increasing because new outbreaks or hosts of TuMV are being reported (Stavolone et al., 1998; Hunter et al., 2002; Chen et al., 2003; Segundo et al., 2003; Farzadfar et al., 2005; Robertson and Ianson, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In an extensive survey conducted in many countries, TuMV was found to be the second most important virus after Cucumber mosaic virus (Tomlinson and Ward, 1987). Moreover, the incidence of TuMV may be increasing because new outbreaks or hosts of TuMV are being reported (Stavolone et al., 1998; Hunter et al., 2002; Chen et al., 2003; Segundo et al., 2003; Farzadfar et al., 2005; Robertson and Ianson, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Observations carried out on inoculated plants indicate a slow development of the disease and limited spatial distribution of the virus in plant tissues, even if TuMV infection resulted in characteristic symptoms, like necrotic spots and mosaics, corresponding to those observed by other authors Walkey 1990, Hunter et al 2002). Another point is that the intensity of the symptoms and the course of a disease could be different when observed in the field, because infection with TuMV usually makes cabbage more prone to coinfection by other pathogens, resulting in greater damage to the crop (Hardwick et al 1994, Hunter et al 2002, Spence et al 2007. It can be concluded that both tested TuMV isolates were infective to 'Amager' and 'Langedijker' cabbage cultivars.…”
Section: Resultsmentioning
confidence: 99%
“…Die Resistenzevaluierungen innerhalb der Familie der Brassicaceae haben gezeigt, dass die im Anbau befindlichen Kohlgemüse überwiegend anfällig gegen das Turnip mosaic virus (TuMV) sind (Walkey & Pink 1988, Krämer et al 1995 ist es zur Vermeidung von Ertrags-und Qualitätsverlus-ten notwendig, die Resistenz gegen dieses Virus zu verbessern (Hunter et al 2002, Krämer et al 2003 …”
Section: Diskussionunclassified
“…Die im Rahmen der Evaluierung gefundenen Resistenzen wurden durch konventionelle und/oder biotechnologische Methoden, wie der somatischen Hybridisierung, in die Kulturform des Kohls übertragen. (Hunter et al 2002;Krämer et al 2003). Das TuMV ist weltweit verbreitet und gehört zur Gruppe der Potyviren.…”
unclassified